Automated parallel GUI testing as a service for mobile applications. Issue 10 (19th June 2018) - Ali, Amira; Maghawry, Huda Amin; Badr, Nagwa
Abstract: Recently, testing mobile applications is gaining much attention due to the widespread of smartphones and the tremendous number of mobile applications development. It is essential to test mobile applications before being released for the public use. Graphical user interface (GUI) testing is a type of mobile applications testing conducted to ensure the proper functionality of the GUI components. Typically, GUI testing requires a lot of effort and time whether manual or automatic. Cloud computing is an emerging technology that can be used in the software engineering field to overcome the defects of the traditional testing approaches by using cloud computing resources. As a result, testing‐as‐a‐service is introduced as a service model that conducts all testing activities in a fully automated manner. In this paper, a system for mobile applications GUI testing based on testing‐as‐a‐service architecture is proposed. The proposed system performs all testing activities including automatic test case generation and simultaneous test execution on multiple virtual nodes for testing Android‐based applications. The proposed system reduces testing time and meets fast time‐to market constraint of mobile applications. Moreover, the proposed system architecture addresses many issues such as maximizing resource utilization, continuous monitoring to ensure system reliability, and applying fault‐tolerance approach to handle occurrence of any failure.